A place-based approach to social entrepreneurship for social integration – Cases from Norway and Sweden. (June 2018) - Hermelin, Brita; Rusten, Grete
Social innovation has gained an important position in policy agendas at the international, national, and local levels. The article investigates two empirical cases of local social entrepreneurship initiatives in two comparable small towns located in Norway and in Sweden. These projects endeavour for social integration of young persons into education programmes and adult persons into work. Through these empirical cases, this article aims to conceive how place conditions the capacities and practices of social entrepreneurship. The place-based approach of the discussion shows how the interplay of local and multiscalar relations impacts social entrepreneurship initiatives. The analysis of the empirical cases involves considering the role of the local context as well as the institutional systems of the welfare states and wider policy regimes endorsing social investment strategies. The discussion employs a model for organisational arrangements focusing on capacities of learning, exploiting, and linking. The capacity of linking across organisations and sector boundaries is found to be a particularly intriguing aspect of the investigated social entrepreneurship initiatives and is something that the place-based approach of the article is able to explicate.